2010
DOI: 10.1080/00222931003632732
|View full text |Cite
|
Sign up to set email alerts
|

Locomotory activity and orientation ofMesobuthus gibbosus(Scorpiones: Buthidae) in central Aegean Archipelago

Abstract: This study explores the locomotory activity of Mesobuthus gibbosus on Koufonisi Island (central Aegean). We measured orientation of movement, shelter selection and abiotic factors that influence locomotive activity throughout the circadian and lunar cycles. Our results show M. gibbosus is a highly active and negatively phototactic species with sexually dimorphic patterns of movements that are related to maternal protective behaviour. Male scorpions disperse more widely, apparently as a function of mate search,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…[ 122 , 123 ]). A male-longer metasoma could alternatively be a by-product of different selection pressures on more sedentary females compared to more vagile males [ 121 , 124 , 125 ], resulting in different foraging [ 126 ] or defense/escape [ 49 ] tactics. We suspect that sexual selection has shaped the dimorphism of this body component in H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 122 , 123 ]). A male-longer metasoma could alternatively be a by-product of different selection pressures on more sedentary females compared to more vagile males [ 121 , 124 , 125 ], resulting in different foraging [ 126 ] or defense/escape [ 49 ] tactics. We suspect that sexual selection has shaped the dimorphism of this body component in H .…”
Section: Discussionmentioning
confidence: 99%
“…Intersexual and interspecific differences in pectine structure may reflect, for example, differing degrees of vagility in scorpions. Males typically travel more and occupy larger home ranges than females, particularly during the breeding season when males are searching for mates, and given the sensory importance of the pectines, exaggeration of this body component in males is reasonable [ 58 , 124 , 130 132 ]. However, the pectines may also function in prey detection [ 133 , 134 ], and therefore could be under the influence of natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…This change in activity during the lunar cycle is perhaps because of nocturnal visual predators (Warburg & Polis, 1990). Adult scorpions but not juveniles reduced activity during high illumination of the lunar cycle for Buthus occitanus (Skutelsky, 1996) and Mesobuthus gibbosus (Brullé, 1832) (Kaltsas & Mylonas, 2010). However, not all scorpions differ in activity because of the lunar cycle including Centruroides sculpturatus Ewing, 1928(Hadley & Williams, 1968 and S. mesaensis (Polis, 1980a).…”
Section: Discussionmentioning
confidence: 99%
“…0-0750) at least 18 days before testing. Previous studies found that painting the mesosomata did not seem to affect the activity of the scorpions (Tourtlotte 1974;Kaltsas and Mylonas 2010).…”
Section: Animalsmentioning
confidence: 91%